Recursos de Tecnologia Assistiva para a educação musical e o desenvolvimento cultural de estudantes com cegueira - Marins, Plínio César (Universidade Federal de São Carlos, 2024)
Music education has deep historical roots, and its status as a mandatory component in Brazil’s curriculum underscores its significance. For blind students, Braille Music Notation is essential in ensuring access to knowledge and autonomy in the teaching and learning process. However, one of the contemporary challenges in music education for Special Education students is the lack of instructional resources that are either adapted or specifically developed for this purpose. This research proposed the creation of an innovative Assistive Technology resource, utilizing 3D printing for the music education of visually impaired individuals, aiming to expand access to this artistic language and explore its impacts on students' cultural development. Methodologically applied in nature, with a qualitative approach and exploratory objective, the research included a literature review, detailed descriptions of the resource production, and the conduct of a case study. Resource development followed a user-centered protocol, involving 3D-printed material prototyping and the adaptation of songs and exercises into Braille notation. The case study was conducted with a blind third-year high school student from a state school in the interior of São Paulo, who used the developed resources. Data collection involved field observations, recordings, and interviews, with analysis grounded in the Cultural Historical Theory of Human Development and Historical-Dialectical Materialism, seeking to understand the social and historical influences on the student’s musical knowledge construction. The research resulted in the development of two 3D-printed instructional resources and the transcription of 23 songs into Braille Music Notation, along with additional exercises for music education. These materials were evaluated and tested by the student, highlighting the importance of Assistive Technology within Special Education. Furthermore, it was found that the student was able to assimilate musical concepts through the use of these developed resources, with an observed increase in cultural engagement and social interaction within her community.
Assistive Technology resources for musical education and the cultural development of students with blindness
Keywords: Educação Especial; Cegueira; Material Didático; Musicografia Braille; Impressão 3D; Ensino de Música; Special Education; Blindness; Educational Material; Braille Music Notation; 3D Printing; Music Teaching; LINGUISTICA, LETRAS E ARTES::ARTES::MUSICA; CIENCIAS HUMANAS::EDUCACAO; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::DESENVOLVIMENTO DE PRODUTO; OUTROS; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL